Effect of the Cooperative Learning Model through E-Module regarding Third Stage of Labor Care on the Increase in Knowledge, Skills and Learning Motivation among Midwifery D-III Students - Arweni Puspita Sari; Mardiana Ahmad; Prastawa Budi; Sutinah Made; Andi Nilawati Usman; Syafruddin Syarif; Jufriadi Jufriadi (Poltekkes Kemenkes Palu, 2023)
The era of the industrial revolution 4.0 has led to technological developments, especially in the world of education. This era emphasizes the pattern of digital economy, artificial intelligence, big data, robotics, and so on or commonly known as the phenomenon of disruptive innovation, for example the use of Android as a mobile learning medium. This study aims to determine the effect of the cooperative learning model thorugh e-module regarding third stage of labor care on the increase in knowledge, skills, and learning motivation among midwifery D-III students. This was a quantitative study with a pre-experimental approach using a two-group pre-test- post-test design. The results showed that the majority of respndents in the two groups of variables before being given treatment had poor knowledge as many as 33 respondents (73.3%) and 34 respondents (75.6%), all respondents had poor skills, and the majority had low motivation as many as 39 respondents (86.7%) and 45 respondents (100%). The statistical test for knowledge, skills and motivations variables obtained the same p value of 0.000 <0.05. Thus, the research hypothesis was accepted. There was an effect of the cooperative learning model with e-module regarding third stage of labor care on the increase in knowledge, skills and learning motivation among midwifery DIII students.